2020
DOI: 10.1007/s11071-020-05854-6
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility and COVID-19 initial dynamics

Abstract: Countries in Europe took different mobility containment measures to curb the spread of COVID-19. The European Commission asked mobile network operators to share on a voluntarily basis anonymised and aggregate mobile data to improve the quality of modelling and forecasting for the pandemic at EU level. In fact, mobility data at EU scale can help understand the dynamics of the pandemic and possibly limit the impact of future waves. Still, since a reliable and consistent method to measure the evolution of contagi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 20 publications
3
97
0
3
Order By: Relevance
“…We use the number of COVID-19 cases as a proxy for a reduction in automotive traffic and a decrease in industrial activities. Some recent studies [26,27] have shown a strong association (R 2 > 0.89) between COVID-19 incidence and mobility. These authors showed that the higher the mobility the higher the number of contagions.…”
Section: Introductionmentioning
confidence: 91%
“…We use the number of COVID-19 cases as a proxy for a reduction in automotive traffic and a decrease in industrial activities. Some recent studies [26,27] have shown a strong association (R 2 > 0.89) between COVID-19 incidence and mobility. These authors showed that the higher the mobility the higher the number of contagions.…”
Section: Introductionmentioning
confidence: 91%
“…The indicator adopts a weekly time frequency (separating between week days and weekend mobility), and uses the NUTS3 regions as a geographic reference. For more information about the connectivity matrix and its applications, we redirect the interested reader to Iacus et al (2020a).…”
Section: Connectivity Matrixmentioning
confidence: 99%
“…Fig. 1 The simplified logic behind the anomaly detection strategy: a sudden drop of the volume of the cell may identify an anomaly, while one within the natural variability of the data not Some applications of these data to different contexts than the one presented here can be found in Santamaria et al (2020) and Iacus et al (2020aIacus et al ( , 2020b.…”
Section: The Mobile Positioning Datamentioning
confidence: 99%